2019
DOI: 10.1186/s12967-019-1906-3
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for mitochondrial-derived peptides humanin and MOTS-c in patients with Q fever fatigue syndrome and chronic fatigue syndrome

Abstract: Background Q fever fatigue syndrome (QFS) is a well-documented state of prolonged fatigue following around 20% of acute Q fever infections. It has been hypothesized that low grade inflammation plays a role in its aetiology. In this study, we aimed to identify transcriptome profiles that could aid to better understand the pathophysiology of QFS. Methods RNA of monocytes was collected from QFS patients (n = 10), chronic fatigue syndrome patients (CFS, n = 10), Q fever ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…During the Dutch Q fever outbreak (2009-2012), our group demonstrated that QFS patients exhibit signs of altered immunity through the monocyte-derived cytokines Tumor Necrosis Factor (TNF)α, interleukin (IL)-1β, and especially IL-6, together with the interferon (IFN)γ-axis (12)(13)(14). In addition, we found that monocytes of both QFS patients and CFS patients show decreased expression of mitochondrial derived peptide (MDP)-coding genes MT-RNR1 and MT-RNR2, resulting in a decreased production of humanin (MT-RNR2) (15).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…During the Dutch Q fever outbreak (2009-2012), our group demonstrated that QFS patients exhibit signs of altered immunity through the monocyte-derived cytokines Tumor Necrosis Factor (TNF)α, interleukin (IL)-1β, and especially IL-6, together with the interferon (IFN)γ-axis (12)(13)(14). In addition, we found that monocytes of both QFS patients and CFS patients show decreased expression of mitochondrial derived peptide (MDP)-coding genes MT-RNR1 and MT-RNR2, resulting in a decreased production of humanin (MT-RNR2) (15).…”
Section: Discussionmentioning
confidence: 98%
“…Dennis et al showed that the 4E-BP1 phosphorylation was inhibited when intracellular adenosine triphosphate (ATP) levels were lowered (48). Interestingly, chronic fatigue has previously been associated with a decrease in cell metabolism (15,18,49,50), and PBMCs of CFS patients showed a decrease in mitochondrial function compared to PBMCs of HC when stressed (51)(52)(53). Axis inhibition protein (AXIN1), negatively regulates the Wnt signalling pathway by downregulation of β-catenin (54), but has also been identi ed as a scaffold protein that activates TGF-β signalling (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dennis et al showed that the 4E-BP1 phosphorylation was inhibited when intracellular adenosine triphosphate (ATP) levels were lowered (48). Interestingly, chronic fatigue has previously been associated with a decrease in cell metabolism (15,18,49,50), and PBMCs of CFS patients showed a decrease in mitochondrial function compared to PBMCs of HC when stressed (51)(52)(53). Axis inhibition protein (AXIN1), negatively regulates the Wnt signalling pathway by downregulation of β-catenin (54), but has also been identi ed as a scaffold protein that activates TGF-β signalling (55).…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent findings by our group [16] identifying a significantly decreased expression of mitochondrial-derived peptide (MDP)-coding genes MT-RNR1 and MT-RNR2 in QFS patients compared with healthy controls, we investigated the expression of these genes in acute Q fever patients compared with healthy controls, both at the time of infection and follow-up.…”
Section: Methodsmentioning
confidence: 99%